2007
DOI: 10.1111/j.1532-5415.2007.01205.x
|View full text |Cite
|
Sign up to set email alerts
|

Practicing Physician Education in Geriatrics: Lessons Learned from a Train‐the‐Trainer Model

Abstract: Evidence of poor performance in the evaluation and management of common geriatric conditions suggests the need for changing physician behavior in these areas. Traditional lecture-style continuing medical education (CME) has not been shown to be effective. Expert faculty initially trained 60 nonexpert peer educators to conduct small-group, learner-centered CME using tool kits on memory loss, incontinence, and depression. Peer educators presented 109 community-based sessions to 1,309 medical practitioners. Surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 20 publications
(19 reference statements)
0
46
0
1
Order By: Relevance
“…First, using hospitalist peers and local geriatricians likely increased trust in the educational curricula and allowed for strong communication channels between instructors. 25,26 Second, coteaching allowed for hospitalist mentorship. Hospitalists acknowledged their coleaders as mentors and several hospitalists subsequently engaged in new geriatric projects.…”
Section: Discussionmentioning
confidence: 99%
“…First, using hospitalist peers and local geriatricians likely increased trust in the educational curricula and allowed for strong communication channels between instructors. 25,26 Second, coteaching allowed for hospitalist mentorship. Hospitalists acknowledged their coleaders as mentors and several hospitalists subsequently engaged in new geriatric projects.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the project team facilitated 'training days' in each of the participating organisations and monthly follow-up meetings were provided for participants. Levine et al (2007Levine et al ( :1281 also identified that 'toolkits' were important in enabling peer-educators to facilitate learning. The 'train the trainers' model has been successfully used in public health initiatives where large numbers of people, spread across a range of settings, need to be reached.…”
Section: Methodsmentioning
confidence: 99%
“…The project aims included a 'train the trainers' approach in order to effectively cascade learning activity (Levine et al, 2007) and promote a sustainable culture of compassionate care at all levels of an organisation. Members of the project team facilitated 'training days' in each of the participating organisations and monthly follow-up meetings were provided for participants.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations